Motivational interviewing-based health coaching to improve diabetes knowledge and manage blood glucose: A quasi-experimental study - Jafar, Nuurhidayat; Setyawati, Andina; Malasari, Silvia; Grestin Sandy R (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Background: Diabetes management relies significantly on patient knowledge, which affects personal care practices and overall well-being. However, many patients face challenges in managing their condition due to insufficient support and motivation. Objective: This study aimed to evaluate the effectiveness of a motivational interviewing-based health coaching program using the  Focus, Identify, Reflect, Act (FIRA) model in enhancing diabetes knowledge and managing blood glucose, BMI, and blood pressure.Methods: A quasi-experimental study was conducted involving 121 adult participants with type 2 diabetes, allocated into intervention (n = 61) and control (n = 60) groups. The intervention group received six bi-weekly health coaching sessions over three months, based on the FIRA model integrated with motivational interviewing techniques. Pre and post-intervention assessments were conducted to evaluate diabetes knowledge, fasting blood glucose, BMI, and blood pressure. Statistical analysis included paired t-tests for within-group comparisons and independent t-tests or Mann-Whitney U tests for between-group analyses, based on data distribution.Results: The intervention group exhibited a significant improvement in diabetes knowledge (mean change = +3.80; p < 0.0001), while the control group showed a decline (mean change = -2.97; p < 0.0001). A significant reduction in fasting blood glucose was also observed in the intervention group (mean change = -17.00 mg/dL; p = 0.015), in contrast to a non-significant increase in the control group (mean change = +3.00 mg/dL; p = 0.365). No significant changes were found in BMI and systolic blood pressure. Diastolic blood pressure increased significantly in the control group (p = 0.001), while the decrease in the intervention group was not statistically significant (p = 0.432); the between-group difference was also not significant (p = 0.226).Conclusion: Motivational interviewing-based health coaching effectively improves diabetes knowledge and blood glucose management. Further studies are recommended to explore long-term impacts and personalised strategies to optimise patient outcomes.